Recent Advances in Reactions of Propargylamines - Sheng, Xia; Chen, Kaijun; Shi, Chengjin; Huang, Dayun (Synthesis, 2020)
Propargylamines are extremely versatile and common building blocks in the field of chemistry. This review highlights the recent advances made in the reactions of propargylamines between 2009 and 2019. The reaction types are classified into six categories based on the trigger mechanisms: (1) amino moieties as leaving groups, (2) hydrogenation, (3) rearrangement, (4) nucleophilic amines, (5) nucleophilic carbons, and (6) electrophilic alkynes. We hope that this review will promote future research in this area.1 Introduction2 Amino Moieties as Leaving Groups3 Hydrogenation4 Rearrangement5 Nucleophilic Amines6 Nucleophilic Carbons7 Electrophilic Alkynes8 Conclusions
Keywords: mechanisms; leaving groups; nucleophiles; rearrangements; propargylamines; tandem reactions